CONTEXTUAL TEACHING AND LEARNING APPROACH (CTL) IN ENGLISH TEACHING: ITS ADVANTAGES AND DISADVANTAGES - Alfian, Alfian (Universitas Esa Unggul, 2019)
AbstractIntentionally focused on the implementation of Contextual Teaching and Learning, this present study tried to scrutinize how English teacher used seven components of CTL such as constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Both its advantages and disadvantages are also taken into account. This present study is conducted at Islamic Senior High School 4 (MAN 4 Jakarta) the method used in this present study is a descriptive qualitative. The sources of data are taken from the English teachers, and students. For the instrument, the writer used triangulation technique. He did the observation, gave the questionnaire to the students, and did an in-depth interview with the English teacher.The result ofthis present study indicates that the implementation of sevent components of CTL has generally been used by the English teacher. Despite its advantages and disadvantages, it is clearly known from the observation, questionnaire, and interview that the implementation of the CTL components have finely been implemented at MAN 4 Jakarta. Ã‚Â Keywords:Contextual, teaching, learningÃ‚Â AbstrakDifokuskan pada implementasi Pembelajaran Kontekstual, penelitian ini mencoba untuk meneliti bagaimana Guru bahasa Inggris menggunakan tujuh komponen CTL seperti konstruktivisme, penyelidikan, tanya jawab, komunitas belajar, pemodelan, refleksi, dan penilaian otentik. Kelebihan dan kekurangannya juga diperhitungkan.Penelitian ini dilakukan di Madrasah Aliyah Negeri 4 (MAN 4 Jakarta) dan metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Sumber data diambil dari Guru Bahasa Inggris, dan siswa. Untuk instrumen, penulis menggunakan teknik triangulasi. Penulis melakukan pengamatan, memberikan kuesioner kepada para siswa, dan melakukan wawancara mendalam dengan Guru Bahasa Inggris. Hasil penelitian ini menunjukkan bahwa penerapan tujuh komponen CTL secara umum telah digunakan oleh guru bahasa Inggris. Selain kelebihan dan kekurangan dalam penerapannya di dalam kelas, dapat diketahui secara jelas dari pengamatan, kuesioner, dan wawancara bahwa penerapan komponen CTL telah digunakan dengan baik di MAN 4 Jakarta.Ã‚Â Kata kunci: Kontekstual, pengajaran, pembelajaran